PENGEMBANGAN MODEL PEMBELAJARAN BIOLOGI BERORIENTASI ETNOPEDAGOGI PADA MAHASISWA CALON GURU - Iwan Setia Kurniawan; Uus Toharudin (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2017)
This study aimed to describe the ability of student teachers of biology at Pasundan University in developing learning models oriented of ethno-pedagogy. This research used a quasi-experimental with quantitative descriptive analysis techniques, data obtained based on the results of data analysis are described for obtaining information or a description of the results of this study. The population in this study as many as 197 students were divided into 38 groups, the sample in this study as many as 28 groups. Data collected by the non-test, the data obtained from a document or report student assignments given a score based on the indicators are divided into several aspects of the assessment, the questionnaire responses of students and teacher ratings. The results showed that the ability of student teachers of biology in developing the oriented of ethno-pedagogy learning models included in both categories, with an average score of 78.04. The average score highest on aspects of the grammar used by students in developing learning models oriented of ethno-pedagogy at 83.21 and the lowest score associated with the creative aspect of student groups in developing learning models oriented of ethno-pedagogy at 74.84. The response of students to the development oriented of ethno-pedagogy learning model is quite good as many as 74.96% of students than expected. Assessment of teachers in general about the development oriented of ethno-pedagogy learning model is quite good, teachers want their socialization and the need for further development of the learning model with ethno- pedagogy is based on the local wisdom.Penelitian ini bertujuan untuk mendeskripsikan kemampuan mahasiswa calon guru biologi di Universitas Pasundan dalam mengembangkan model pembelajaran berorientasi etnopedagogi. Penelitian ini menggunakan metode kuasi eksperimen dengan teknik analisis deskriptif kuantitatif, data yang diperoleh berdasarkan hasil analisis data dideskripsikan untuk memperoleh informasi atau gambaran hasil penelitian ini. Populasi pada penelitian ini sebanyak 197 mahasiswa yang terbagi dalam 38 kelompok, sampel dalam penelitian ini sebanyak 28 kelompok. Teknik pengumpulan data dilakukan dengan nontest, data diperoleh dari dokumen atau laporan tugas mahasiswa yang diberikan skor berdasarkan indikator-indikatornya yang terbagi kedalam beberapa aspek penilaian, kuesioner respon mahasiswa dan penilaian guru. Hasil penelitian menunjukan bahwa kemampuan mahasiswa calon guru biologi dalam mengembangkan model pembelajaran berorientasi etnopedagogi termasuk kategori dalam baik, dengan skor rata-rata sebesar 78,04. Skor rata-rata tertinggi yaitu pada aspek tatabahasa yang digunakan oleh mahasiswa dalam mengembangkan model pembelajaran berorientasi etnopedagogi sebesar 83,21 dan skor terendah terkait dengan aspek kreativitas kelompok mahasiswa dalam mengembangkan model pembelajaran berorientasi etnopedagogi sebesar 74,84. Respon mahasiswa terhadap pengembangan model pembelajaran berorientasi etnopedagogi cukup baik yaitu sebanyak 74,96% mahasiswa dari yang diharapkan. Penilaian guru secara umum mengenai pengembangan model pembelajaran berorientasi etnopedagogi cukup baik, guru menghendaki adanya sosialisasi dan perlu adanya pengembangan model pembelajaran lebih lanjut dengan berbasis etnopedagogi yang dilandasi dengan kearifan lokal (local wisdom).